2016
DOI: 10.1016/j.jsat.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy Improves Treatment Outcomes for Prescription Opioid Users in Primary Care Buprenorphine Treatment

Abstract: To determine whether treatment outcomes differed for prescription opioid and heroin use disorder patients, we conducted a secondary analysis of a 24-week (N = 140) randomized trial of Physician Management (PM) or PM plus Cognitive Behavioral Therapy (CBT) in primary care buprenorphine/naloxone treatment. Self-reported opioid use and urine toxicology analyses were obtained weekly. We examined baseline demographic differences between primary prescription opioid use patients (n = 49) and primary heroin use patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…This may include incorporating religion and spirituality, family therapy, case management, collaboration with probation and parole, and vocational training. Cognitive behavioral therapy (Kumari et al, 2016; Moore et al, 2016) and contingency management (Ling et al, 2013) have previously shown effectiveness with community-based samples and may have potential – if culturally adapted to address the specific substance use and mental health needs of criminal justice-involved African American men. Finally, while medication-based interventions have shown some efficacy (Carroll & Weiss, 2017) and effectiveness (Damian et al, 2017), compared to Whites, African Americans are disproportionately underrepresented in pharmacotherapy studies (Hansen et al, 2016; Mitchell et al, 2016).…”
Section: 0 Discussionmentioning
confidence: 99%
“…This may include incorporating religion and spirituality, family therapy, case management, collaboration with probation and parole, and vocational training. Cognitive behavioral therapy (Kumari et al, 2016; Moore et al, 2016) and contingency management (Ling et al, 2013) have previously shown effectiveness with community-based samples and may have potential – if culturally adapted to address the specific substance use and mental health needs of criminal justice-involved African American men. Finally, while medication-based interventions have shown some efficacy (Carroll & Weiss, 2017) and effectiveness (Damian et al, 2017), compared to Whites, African Americans are disproportionately underrepresented in pharmacotherapy studies (Hansen et al, 2016; Mitchell et al, 2016).…”
Section: 0 Discussionmentioning
confidence: 99%
“…While brief motivational interviewing was not found to be superior to other interventions for reduction of opioid usage, previous studies have investigated the effectiveness of other behavioral interventions, such as cognitive behavioral therapy (CBT), on the reduction of opioid usage. CBT has been shown to increase abstinence from drugs in those addicted to prescription opioids [ 40 ] and to be superior to methadone drug counseling at increasing abstinence from non-prescription opioids [ 41 ]. These results, while promising, are in contrast to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used biological markers to determine compliance to known dosages of treatment medications or measure nonabstinence during treatment Baros, Latham, Moak, Voronin, & Anton, 2007;Gerra, Fantoma, & Zaimovic, 2006;Kumari et al, 2016;McDermott et al, 2015;Moore et al, 2016;Pal Singh Balhara & Jain, 2012). Other studies have focused on meaningful comparisons regarding treatment modalities, efficacy methadone vs. bup/nal, and determination of risk factors for compliance and treatment success.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on meaningful comparisons regarding treatment modalities, efficacy methadone vs. bup/nal, and determination of risk factors for compliance and treatment success. Many of these studies have used short follow-up periods, and researchers have focused largely on retention rates, chart reviews, instances of buprenorphine administration, interviews, self-report of heroin use and criminal activity, and telephone or internet communication, to measure adherence and abstinence (Fareed et al, 2014;Maas, Barton, Maskrey, Pinto, & Holland, 2013;Mattick et al, 2014;Moore et al, 2016;Parran et al, 2010;Tkacz, Severt, Cacciola, & Ruetsch, 2012).…”
Section: Introductionmentioning
confidence: 99%